Foam metal-based modified composite material as well as preparation method and application thereof

By depositing NiO, CdSe and CuS layers on the surface of the three-dimensional foam nickel metal-based material, and converting NO3- in the water into N2 by photoelectro-catalytic reaction, the problem of difficulty in efficiently removing nitrate nitrogen in the prior art is solved, and an efficient and environmentally friendly water purification effect is achieved.

CN119819327APending Publication Date: 2025-04-15张子怡
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510097172.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove nitrate nitrogen (NO3-) in water bodies, and by-products such as nitrite (NO2-) and ammonia (NH3) can also cause pollution to the environment.

Method used

Using a three-dimensional foam nickel metal-based photoelectrically modified composite material, Nickel oxide (NiO), cadmium selenide (CdSe) and copper sulfide (CuS) layers were deposited on the surface of the nickel matrix, and NO3- was converted into nitrogen (N2) by photoelectric catalytic reaction.

Benefits of technology

The conversion and selectivity of nitrate nitrogen is significantly improved, and the efficient water purification effect is achieved. The photoelectrocatalytic materials can be reused many times to maintain extremely high removal rates and selectivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the foam metal-based modified composite material and the preparation method and application thereof, by preparing the CuS / CdSe / NiO / NF composite material, the conversion rate and selectivity of nitrate nitrogen can be effectively improved under the photoelectric condition, the catalytic efficiency is remarkably improved, and the effect of purifying a water body is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectrocatalytic water purification and relates to a foam metal-based modified composite material, specifically a three-dimensional foam nickel metal-based photoelectrocatalytic modified composite material. Background Art

[0002] With the rapid development of industry and agriculture, the demand for fertilizers and industrial materials has greatly increased, resulting in the - ) has also accumulated in water bodies year by year. In agricultural production, nitrogen fixation technology is used to convert N2 in the atmosphere into NH3 for fertilizer production. However, due to excessive fertilization and low utilization efficiency of nitrogen fertilizers, NO3 - The content in groundwater, lakes and rivers far exceeds the limit of natural purification. Large amounts of NO3 are discharged during industrial manufacturing and metal processing. - Due to the large-scale use of nitrogen fertilizers, the deposition of gaseous nitrogen oxides and industrial production emissions, NO3 - The water environment has been polluted to varying degrees. For example, industrial wastewater, domestic sewage and urban sewage contain a large amount of ammonia nitrogen and organic nitrogen oxides. Direct discharge or discharge of such sewage without treatment will cause surface water pollution such as lakes and rivers. After seepage into the ground, the organic nitrogen in the sewage is mineralized and adsorbed during the groundwater circulation process, and oxidized into NO3 by microorganisms. - Cause water pollution.

[0003] NO3 - Long-term accumulation in the environment causes varying degrees of damage to the soil, water and atmospheric environment. Most of the nutrients not absorbed by crops after excessive nitrogen and phosphorus fertilizers are applied remain in the soil, causing soil compaction and reduced water holding capacity, affecting soil fertility. - Entering the soil in the form of pollutants will reduce soil acidity, directly affecting crop growth, and further pollute surface water and groundwater under the action of rainfall and infiltration.

[0004] Various types of industrial wastewater and domestic sewage are irrationally discharged into rivers, oceans and other water bodies, including excessive NO3 - The surface water will be greatly affected. - Excessive content is one of the important reasons for eutrophication of water bodies. - Excessive input of nutrients into water bodies will cause rapid growth of algae, which will consume a large amount of dissolved oxygen in the water, causing red tides, algal blooms and other phenomena that destroy the living environment of aerobic aquatic organisms, and produce black and smelly pollution, reducing the utilization efficiency of water resources and the environmental and economic benefits.

[0005] The ideal product of electrochemical catalytic reduction denitrification is non-toxic and harmless N2, which is produced through a 5-electron reaction process.

[0006] NO3 - + 6H + +5e - →1 / 2N2 + 3H2O; side reaction, NO3 - + 9H + +8e - →NH3 + 3H2O, due to nitrite (NO2 - ) and ammonia (NH3) can also pose a threat to the environment and humans. - At the same time, the production of such by-products should be avoided or reduced.

[0007] CN202111311948 discloses a photoelectrocatalytic system and application for efficiently removing nitrate nitrogen from a high-salt system, and provides a photoelectrocatalytic system and application for efficiently removing nitrate nitrogen from a high-salt system, including a photoanode, a photocathode, an ultraviolet light source, an electrolytic cell and a DC power supply; the electrolytic cell contains a high-salt system electrolyte containing nitrate nitrogen, and the photoanode and the photocathode are arranged in the electrolytic cell and are respectively connected to the DC power supply; the photoanode is a titanium dioxide nanotube array made with a titanium metal sheet as a substrate; the photocathode is a palladium and copper bimetallic electrode. The present invention uses the photocathode to reduce nitrate as the main reaction, and uses the Cl· generated by the photoanode to oxidize the byproduct NH4 of the photocathode + It is N2, thus reducing nitrate to nitrogen with high selectivity and efficiency. The removal rate of nitrate nitrogen and the selectivity of generating nitrogen are high, and basically no by-products such as nitrite ions and ammonia nitrogen are produced. Nitrate nitrogen is completely removed. It is an efficient and environmentally friendly nitrate nitrogen removal system in a high-salt environment, and is particularly suitable for treating nitrate nitrogen in the desorption liquid of anion exchange resin. Summary of the invention

[0008] Based on the above cognition, the present invention provides a foam metal-based modified composite material and a preparation method and application thereof. By preparing a CuS / CdSe / NiO / NF composite material, under external bias illumination conditions, CdSe absorbs energy to form photogenerated electrons and photogenerated holes, wherein the holes move toward the NiO direction and the electrons move toward the catalytic surface, thereby promoting the conversion of nitrate nitrogen, effectively improving the conversion rate and selectivity of nitrate nitrogen, and significantly improving the catalytic efficiency to achieve the effect of water purification.

[0009] Specifically: a foam metal-based modified composite material, the material uses a three-dimensional foam nickel metal material as a matrix, and the surface is composed of a three-dimensional foam nickel matrix, a nickel oxide layer, a CdSe layer and a surface-loaded CuS nanocatalytic layer from bottom to top.

[0010] The nickel oxide layer has a thickness of 10-20 nm and is obtained by immersion in oxidizing acid.

[0011] The thickness of the CdSe layer is 400-500 nm and is obtained by electrochemical deposition.

[0012] The CuS nanocatalytic layer is obtained by chemical reduction.

[0013] A method for preparing a foam metal-based modified composite material comprises the following steps: (1) The three-dimensional nickel foam substrate is subjected to surface pretreatment, wherein the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment, wherein the solution used for the pickling is 2-2.2 mol / L hydrochloric acid, the time is 10-15 min, and the temperature is 10-20° C.; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 8-10 wt.% hypochlorous acid solution, the time is 4-5 min, and the temperature is 10-20° C.

[0014] (2) Prepare a cadmium selenide electrodeposition solution, which consists of 0.4-0.5mmol / L SeO2, 0.1-0.2mol / L CdSO4, 0.05-0.075mol / L tartaric acid, 0.2-0.24mol / L sodium sulfate and deionized water. Use sulfuric acid to adjust the pH of the electrodeposition solution to 4.5-5. Use a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30mV / s, the liquid temperature is 18-20℃, and the electrolysis time is 40-45min.

[0015] (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 7-8 mmol / L copper nitrate, 4-5 mmol / L hydroxyethylidene diphosphonic acid, 12-14 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 50-60° C. for 24-36 hours, cooling it naturally, washing it with deionized water and drying it, and obtaining a photoelectric composite material.

[0016] The application of the composite material in a photoelectrocatalytic system is specifically the removal of nitrate nitrogen in wastewater.

[0017] The present invention uses nickel foam as the substrate of the photoelectrode, which has the characteristics of high applicability and plasticity. First, the surface of the nickel foam is pretreated, and the pretreatment includes acid washing, organic solution washing, deionized water washing and acid soaking treatment. The purpose of the first step of acid washing is to remove the natural nickel oxide layer on the surface of the nickel foam, and the purpose of organic solution washing and deionized water washing is cleaning. The acid soaking uses an oxidizing hypochlorous acid solution. By immersing the nickel foam on the clean surface in an oxidizing acid solution, a relatively regular and orderly nickel oxide film can be obtained. The thickness of the nickel oxide is about 10-20nm, and the thickness is relatively uniform. The more uniform the thickness of the nickel oxide, the more conducive to the subsequent uniform deposition of cadmium selenide. Those skilled in the art should know that NiO, as a p-type semiconductor that transfers holes, has a wide band gap (3.6-4.0 eV), good thermal stability and chemical stability, and its valence band position is 0.45 V (vs NHE), which is a good electron donor. These characteristics determine that nickel oxide is expected to become a promising photocathode material, but NO3 in wastewater - The only contact mode with nickel oxide is adsorption, and the adsorption amount is relatively small, resulting in weak light absorption ability of the photoelectrode. Therefore, the NiO photocathode has the disadvantages of low current density and low comprehensive utilization efficiency of sunlight.

[0018] Based on this, the present invention deposits CdSe on the surface of NiO by electrochemical means. CdSe is a light-absorbing semiconductor with the characteristics of high absorption coefficient for solar spectrum, high efficiency of photogenerated charge separation, and strong ability to reduce photogenerated electrons. In addition, its energy band position is adjustable and has good stability in an aqueous environment. CdSe has a suitable band gap width (1.7 eV), which is very beneficial to the absorption of sunlight. There are many methods for preparing CdSe, such as spraying, evaporation, chemical bath and other methods, but the above methods are more suitable for rod electrodes or plate electrodes and can obtain a uniform film layer. However, for foamed nickel metal, it is difficult to obtain a uniform film layer by the above methods. Electrochemical means obtain the desired semiconductor material by reduction reaction on the cathode under the promotion of electric potential. The electrochemical deposition process is single and has fewer side reactions. Therefore, CdSe has high purity, uniform film thickness, and the overall preparation process is continuous, simple and practical, with low energy consumption.

[0019] The present invention uses SeO2 as Se source, CdSO4 as Cd source, tartaric acid as complexing acid agent, and sodium sulfate as electrolyte. The reaction process can be simply explained as the H2SeO3 in the electrolyte undergoes a reduction reaction to form Se 2- , then with Cd 2+The reaction forms a CdSe film on the NiO surface. When the CdSe film is electrochemically deposited, the potential range is between -0.9 and -0.4 V. The thickness of the film is about 400-500 nm. The thickness of the film is related to the deposition time and the side reaction. Although the thickness of CdSe increases with the increase of electrodeposition time, the CdSe film in the electrolyte will react with H2SeO3 to form Se for the second time, which causes the film to fall off. The reaction is H2SeO3+2CdSe+4H + →3Se+2Cd 2+ +3H2O, the pH of the electrolyte of the present invention is 4.5-5, and contains tartaric acid complexing agent, which can effectively reduce the above-mentioned side reactions, thereby obtaining a thicker CdSe. The corresponding technical effects can be obtained from Example 2 and Comparative Example 1.

[0020] Beneficial technical effects: The present invention provides a CuS / CdSe / NiO / NF photoelectric system that can effectively improve the conversion rate and selectivity of nitrate nitrogen. The photoelectric catalytic material can be reused many times and maintain an extremely high removal rate and selectivity, thereby stably and efficiently achieving the degradation of nitrate nitrogen in wastewater. DETAILED DESCRIPTION Example 1

[0021] A method for preparing a foam metal-based modified composite material comprises the following steps: (1) The three-dimensional nickel foam substrate is subjected to surface pretreatment, wherein the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment, wherein the solution used for the pickling is 2 mol / L hydrochloric acid, the time is 10 min, and the temperature is 10°C; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 8-wt.% hypochlorous acid solution, the time is 4 min, and the temperature is 10°C.

[0022] (2) Prepare a cadmium selenide electrodeposition solution, which consists of 0.4mmol / L SeO2, 0.1mol / L CdSO4, 0.05mol / L tartaric acid, 0.2mol / L sodium sulfate and deionized water. Use sulfuric acid to adjust the pH of the electrodeposition solution to 4.5. Use a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30 mV / s, the liquid temperature is 18°C, and the electrolysis time is 40min.

[0023] (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 7 mmol / L copper nitrate, 4 mmol / L hydroxyethylidene diphosphonic acid, 12 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 50° C. for 24 h, cooling it naturally, washing it with deionized water and drying it to obtain a photoelectric composite material. Example 2

[0024] A method for preparing a foam metal-based modified composite material comprises the following steps: (1) The three-dimensional nickel foam substrate is subjected to surface pretreatment, and the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment. The solution used for the pickling is 2.1 mol / L hydrochloric acid, the time is 12.5 min, and the temperature is 15°C; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 9 wt.% hypochlorous acid solution, the time is 4.5 min, and the temperature is 15°C.

[0025] (2) Prepare a cadmium selenide electrodeposition solution, which consists of 0.45mmol / L SeO2, 0.15mol / L CdSO4, 0.0625mol / L tartaric acid, 0.22mol / L sodium sulfate and deionized water. Use sulfuric acid to adjust the pH of the electrodeposition solution to 4.75. Use a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30mV / s, the liquid temperature is 19℃, and the electrolysis time is 42.5min.

[0026] (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 7.5 mmol / L copper nitrate, 4.5 mmol / L hydroxyethylidene diphosphonic acid, 13 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 55° C. for 30 h, cooling it naturally, washing it with deionized water and drying it to obtain a photoelectric composite material. Example 3

[0027] A method for preparing a foam metal-based modified composite material comprises the following steps: (1) The three-dimensional nickel foam substrate is subjected to surface pretreatment, and the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment. The solution used for the pickling is 2.2 mol / L hydrochloric acid, the time is 15 min, and the temperature is 20°C; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 10 wt.% hypochlorous acid solution, the time is 5 min, and the temperature is 20°C.

[0028] (2) Prepare a cadmium selenide electrodeposition solution, which consists of 0.5mmol / L SeO2, 0.2mol / L CdSO4, 0.075mol / L tartaric acid, 0.24mol / L sodium sulfate and deionized water. Use sulfuric acid to adjust the pH of the electrodeposition solution to 5. Use a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30mV / s, the liquid temperature is 20℃, and the electrolysis time is 45min.

[0029] (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 8 mmol / L copper nitrate, 5 mmol / L hydroxyethylidene diphosphonic acid, 14 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 60° C. for 36 hours, cooling it naturally, washing it with deionized water and drying it to obtain a photoelectric composite material.

[0030] Comparative Example 1 A method for preparing a foam metal-based modified composite material comprises the following steps: (1) The three-dimensional nickel foam substrate is subjected to surface pretreatment, and the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment. The solution used for the pickling is 2.1 mol / L hydrochloric acid, the time is 12.5 min, and the temperature is 15°C; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 9 wt.% hypochlorous acid solution, the time is 4.5 min, and the temperature is 15°C.

[0031] (2) Prepare a cadmium selenide electrodeposition solution, which consists of 0.45mmol / L SeO2, 0.15mol / L CdSO4, 0.22mol / L sodium sulfate and deionized water. Use sulfuric acid to adjust the pH of the electrodeposition solution to 2.15. Use a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30mV / s, the liquid temperature is 19℃, and the electrolysis time is 42.5min.

[0032] (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 7.5 mmol / L copper nitrate, 4.5 mmol / L hydroxyethylidene diphosphonic acid, 13 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 55° C. for 30 h, cooling it naturally, washing it with deionized water and drying it to obtain a photoelectric composite material.

[0033] The photoelectrocatalytic reduction denitrification in the embodiment of the present invention and the comparative example both adopts a three-electrode system and is carried out in an H-type electrolytic cell. The H-type electrolytic cell reactor is divided into a cathode chamber and an anode chamber by an exchange membrane. The working electrode is located in the cathode chamber and corresponds to the platinum plate in the anode chamber in parallel. The potential of the working electrode is recorded by the Ag / AgCl reference electrode. Before the reaction, 100 mL of 50 mM Na2SO4 solution was added to each of the two reaction chambers and aerated with bubbling argon for 10 min to remove dissolved N2 and O2. After sealing, 2 mL of NaNO3 stock solution was injected into the cathode chamber and stirred for 20 min to allow NO3 - The pollutants were evenly dispersed in the electrolyte with a concentration of 22.5 mg / L. After stirring at 400 rpm for half an hour in the dark to reach adsorption-desorption equilibrium, a 300W xenon lamp was used as a light source to simulate sunlight, and a certain bias voltage was applied to the working electrode using an electrochemical workstation to conduct a photoelectrocatalytic experiment. Before the reaction starts, about 2.5 mL of solution is sampled as the initial sample. During the reaction, 2.5 mL of aqueous solution is taken from the cathode chamber at regular intervals for quantitative determination of NO3 in the solution. - , NO2 - and NH3 - .

[0034] NO3 of Example 1 - The removal rate of N2 is 89.3%; the selectivity of N2 is 88.3%; and the removal rate of NO2 is 89.3%. - Selectivity is 5.2%; NH4 + The selectivity is 6.5%, the N2 selectivity is maintained at 88.3%, the stability drops to 83.3%, and the number of uses is approximately equal to 687 times.

[0035] NO3 of Example 2 - The removal rate of is 92.1%; the selectivity of N2 is 92.6%; the removal rate of NO2 is 92.1%; the removal rate of - Selectivity is 3.7%; NH4 + The selectivity is 1.3%, the N2 selectivity is maintained at 92.6%, the stability is reduced to 87.6%, and the number of uses is approximately equal to 726 times.

[0036] NO3 of Example 3 - The removal rate of 88.1%; N2 selectivity is 91.5%; NO2 - Selectivity is 4.3%; NH4 + The selectivity is 4.2%, the N2 selectivity is maintained at 91.5%, the stability drops to 86.5%, and the number of uses is approximately equal to 592 times.

[0037] NO3 of Comparative Example 1 -The removal rate of 43.2%; N2 selectivity is 79.8%; NO2 - Selectivity is 4.2%; NH4 + The selectivity is 16.0%, the N2 selectivity is maintained at 79.8%, the stability drops to 74.8%, and the number of uses is approximately equal to 79 times.

[0038] It can be seen from the test results that Examples 1-3 show excellent performance and high stability in the electrocatalytic reduction denitrification test. In comparison, the photoelectrocatalytic performance and stability of Comparative Example 1 are poor, which may be due to the secondary dissolution of CdSe during the electrolysis process, resulting in film peeling, which in turn makes the stability of the optoelectronic composite material poor.

[0039] The above description is only an example of the implementation mode of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A foam metal-based modified composite material, characterized in that The material uses a three-dimensional nickel foam metal material as a matrix, and the surface thereof is sequentially composed of a three-dimensional nickel foam matrix, a nickel oxide layer, a CdSe layer and a surface-loaded CuS nanocatalytic layer from bottom to top.

2. A foam metal-based modified composite material as claimed in claim 1, characterized in that The nickel oxide layer has a thickness of 10-20 nm and is obtained by immersion in oxidizing acid.

3. A foam metal-based modified composite material as claimed in claim 1, characterized in that The thickness of the CdSe layer is 400-500 nm and is obtained by electrochemical deposition.

4. A foam metal-based modified composite material as claimed in claim 1, characterized in that The CuS nanocatalytic layer is obtained by chemical reduction.

5. A method for preparing a foam metal-based modified composite material, characterized in that The steps include: (1) performing surface pretreatment on the three-dimensional nickel foam substrate, wherein the pretreatment process includes pickling, organic solution washing, deionized water washing and acid soaking treatment, wherein the solution used for pickling is 2-2.2 mol / L hydrochloric acid, the time is 10-15 min, and the temperature is 10-20° C.; the organic solution washing is ethanol soaking; the solution used for the acid soaking treatment is 8-10 wt.% hypochlorous acid solution, the time is 4-5 min, and the temperature is 10-20° C.; (2) preparing a cadmium selenide electrodeposition solution, wherein the electrodeposition solution is composed of 0.4-0.5mmol / L SeO2, 0.1-0.2mol / L CdSO4, 0.05-0.075mol / L tartaric acid, 0.2-0.24mol / L sodium sulfate and deionized water, using sulfuric acid to adjust the pH of the electrodeposition solution to 4.5-5, using a three-electrode system: the nickel foam prepared in step (1) is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and the electrodeposition is carried out in a cyclic voltammetry mode: the potential scanning range is -0.9~-0.4V, the scanning rate is 30mV / s, the liquid temperature is 18-20℃, and the electrolysis time is 40-45min; (3) preparing a copper sulfide precursor solution, wherein the precursor solution includes 7-8 mmol / L copper nitrate, 4-5 mmol / L hydroxyethylidene diphosphonic acid, 12-14 mmol / L thiourea and deionized water, soaking the nickel foam obtained in step (2) in the copper sulfide precursor solution, placing it in a hydrothermal reactor, reacting it at 50-60° C. for 24-36 hours, cooling it naturally, washing it with deionized water and drying it, and obtaining a photoelectric composite material.

6. The use of a foam metal-based modified composite material according to any one of claims 1 to 4, characterized in that Application of the composite material in a photoelectrocatalytic system.

7. The use according to claim 5, characterized in that Used for removal of nitrate nitrogen in wastewater.

Citation Information

Patent Citations

  • Photoelectrocatalysis system for efficiently removing nitrate nitrogen in high-salt system and application

    CN114249399A